Hubungan antara Depresi dengan Lama Menderita Diabetes Melitus Tipe 2 pada Pasien Rawat Jalan di RSUD Karangasem Bali - Sagung Putri Permana Lestari M.P.; Desak Putu Citra Udiyani; I Gede Putu Ryan Adipathyama Perdana (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Depression is a medical illness that could interfere with a person's way of thinking, feeling, and acting. People with depression usually lose interest in carrying out daily activities. Type 2 diabetes mellitus is a condition which the treatment takes a lifetime. Patients with type 2 diabetes mellitus have a risk of experiencing some complications that will worsen the prognosis of the disease. This study aims to assess the relationship between depression and the length of time of suffering type 2 diabetes mellitus in outpatients at the Karangasem Regional General Hospital, Bali. Analytic observational study and a cross-sectional approach was used. The research was conducted from November 2021 – to January 2022 with a purposive sampling technique and obtained 66 samples. The data collection method used primary data from interviews with people with type 2 diabetes mellitus. Data was analised univariately and using Spearman rank test. The Kolmogorov test using SPSS showed a significance value of <0.05, so the data was abnormally distributed. Bivariate analysis shows that a p-value < 0.05 was obtained, which suggest that a significant relationship is present between depression and the duration suffered from type 2 diabetes mellitus. The correlation coefficient (r) is -0.664 which means that a strong negative relationship is present. Medical personnels are expected to make efforts to treat patients with type 2 diabetes mellitus without forgetting psychological impact of the patient. Treatment must be obtained by patients with type 2 diabetes mellitus holistically.